The Effectiveness of Posters as A Media for Monitoring and Stimulation of Children's Growth and Development - Lulianthy, Eliyana; Aprina, Tilawaty; Putri, Dwi Khalisa; Purnamasari, Intan (Universitas Muhammadiyah Semarang, 2023)
Disorders of child growth and development have an impact on morbidity throughout the child's life cycle, transmission of poverty between generations and long-term effects that can hinder the pace of development of a country. Nevertheless, as recorded in the 2018 Early Childhood Development Index, more than 95% of early childhood children in Indonesia have physical and learning abilities that are appropriate for their age and stage of development. However, the development of numeracy literacy and emotional social skills are still below 70%. Thereby, knowledge, attitudes and behavior of parents were correlated with the level of stimulation of growth and development in children. Therefore, this mixed method pre-experimental study aimed to investigate the effectiveness of the